Advances in Management Accounting. - Malina, Mary A. (Advances in management accounting, 2017)
Advances in Management Accounting (AIMA) is a publication of quality applied research in management accounting. The journal's purpose is to publish thought-provoking articles that advance knowledge in the management accounting discipline and are of interest to both academics and practitioners.